KONSEP MANUSIA DALAM PSIKOLOGI ISLAM - Tarmizi Situmorang (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2017)
Humans were created as caliphs on this earth. As a caliph, humans have a heavy mandate to be able to devote themselves as servants of Allah SWT and mercy to all nature. In the concept of Islamic Psychology, humans have a nature that has good and bad potential. The nature itself in its history can be approached with two groups of meanings, namely a large meaning that is religious, and the paradigmatic meaning that is knowledge paradigm.Keywords: Human, nature, religious, knowledge.